Response surface design to study the influence of inoculum, particle size and inoculum to substrate ratio on the methane production from Ulex sp. - Costa, J. C. (2016)
Ulex europaeus is one of the world worst invaders vegetal species and its suitability for biogas production is significant. The effect of three factors affecting the Biochemical Methane Potential (BMP, expressed as volume of CH4 per mass of volatile solids of waste) and the biodegradability rate (k, expressed in volume of CH4 per mass of VS and time) of U. europaeus was assessed by a Central Composite Face Centred Design. The BMP varied from 153 L kg1 to 308 L kg1. Inoculum to substrate ratio (ISR) and the type of inoculum had high influence on the final results. k varied from 14 L kg1 d1 to 49 L kg1 d1. The conditions that simultaneously maximized the BMP and k were an inoculum consisting in 55% (v) of granular sludge and 45 % (v) of suspended sludge from a sludge digester, an ISR of 4 g g1, and a particle size of 1.9 mm. Considering the average biomass production in shrub land areas, the potential energy production from U. europaeus is estimated in (36.9 ± 19.3) GJ ha1 yr1. For example, in Europe, a maximum energy supply of 7 EJ yr1 could be achieved from potentially harvestable shrub land areas.